Implementasi Prinsip-Prinsip Muamalah dalam Transaksi Ekonomi: Alternatif Mewujudkan Aktivitas Ekonomi Halal - Maharani, Dewi; Yusuf, Muhammad (Sharia Faculty Islamic Economic Law Study Department, 2021)
Alternatives on Realizing Halal Economic Activities. This study aims to explain the principles of Muamalah in economic transactions as in Al-Quran and Hadith. Halal economic activity plays an important role in economic transactions in Moslem life, which is the main requirement as one of the essences of Islamic teachings. Economic activities carried out by a Moslem are part of worship to Allah the Almighty who is in the framework of aqidah and sharia. Islamic economics aims to achieve happiness in the world and the hereafter through the order of life, to establish equality between humans